2021
DOI: 10.3390/dj9080097
|View full text |Cite
|
Sign up to set email alerts
|

Abrasion Behaviour of Different Charcoal Toothpastes When Using Electric Toothbrushes

Abstract: Objectives: The purpose of this in vitro study was to compare the abrasion behaviour of different charcoal toothpastes when brushing with electric toothbrushes on human enamel. Materials and Methods: A self-designed brushing machine was built using six commercially available electric toothbrushes in abrasion chambers. Each chamber was constantly supplied with a toothpaste–water mix. Pieces of human enamel, which were embedded in PMMA, were brushed for 4 h. Before and after brushing, profilometer measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
4
4
1
2
Order By: Relevance
“…However, ACPs could be too abrasive for daily use and could increase in the surface roughness 12 . Previous studies demonstrated that ACTs are more abrasive than conventional toothpastes 10,11 . However, in the present study, ACPs presented similar surface roughness to that of the fluoride toothpaste (without charcoal particles), expect for fluoride‐free charcoal group 12 …”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…However, ACPs could be too abrasive for daily use and could increase in the surface roughness 12 . Previous studies demonstrated that ACTs are more abrasive than conventional toothpastes 10,11 . However, in the present study, ACPs presented similar surface roughness to that of the fluoride toothpaste (without charcoal particles), expect for fluoride‐free charcoal group 12 …”
Section: Discussioncontrasting
confidence: 49%
“…12 Previous studies demonstrated that ACTs are more abrasive than conventional toothpastes. 10,11 However, in the present study, ACPs presented similar surface roughness to that of the fluoride toothpaste (without charcoal particles), expect for fluoride-free charcoal group. 12 All the toothpastes have hydrated silica as abrasive particles that could create scratches on the tooth surface and increase the surface roughness.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Sendo assim, é importante ressaltar que uma abrasão contínua provoca diminuição na espessura do esmalte dental, influenciando diretamente na cor do dente, que também é alterada em função da deposição de cromóforos provenientes da dieta, e esta deposição pode ser acelerada devido a porosidade e rugosidade superficial do esmalte (Dionysopoulos et al, 2020). Ainda, sabe-se que o esmalte quando está pré-danificado/amolecido é mais facilmente desgastado (Greuling et al, 2021).…”
Section: Discussionunclassified
“…Alguns autores alegam que o tipo da escova de dente, a técnica e o tempo de escovação influenciam tanto na limpeza quanto no desgaste abrasivo do elemento dentário (Dionysopoulos et al, 2020;Greuling et al, 2021;Vural et al, 2021;Osmanaj et al, 2022). Já no estudo de Rodrigues et al, (2019) não houve diferença significativa quanto ao tipo de escova.…”
Section: Discussionunclassified